Genetic Diversity and Potential Paths of Transmission of Mycobacterium bovis in the Amazon: The Discovery of M. bovis Lineage Lb1 Circulating in South America - Carneiro, Paulo Alex; Zimpel, Cristina Kraemer; Pasquatti, Taynara Nunes; Silva-Pereira, Taiana T.; Takatani, Haruo; Silva, Christian B. D. G.; Abramovitch, Robert B.; Sa Guimaraes, Ana Marcia; Davila, Alberto M. R.; Araujo, Flabio R.; Kaneene, John B. (Frontiers in Veterinary Science, 2021)
Bovine tuberculosis (bTB) has yet to be eradicated in Brazil. Herds of cattle and buffalos are important sources of revenue to people living in the banks of the Amazon River basin. A better understanding of Mycobacterium bovis (M. bovis) populational structure and transmission dynamics affecting these animals can significantly contribute in efforts to improve their sanitary status. Herein, we sequenced the whole genome of 22 M. bovis isolates (15 from buffalo and 7 from cattle) from 10 municipalities in the region of the Lower Amazon River Basin in Brazil and performed phylogenomic analysis and Single Nucleotide Polymorphism (SNP)-based transmission inference to evaluate population structure and transmission networks. Additionally, we compared these genomes to others obtained in unrelated studies in the Marajó Island (n=15) and worldwide (n=128) to understand strain diversity in the Amazon and to infer M. bovis lineages. Our results show a higher genomic diversity of M. bovis genomes obtained in the Lower Amazon River region when compared to the Marajó Island, while no significant difference was observed between M. bovis genomes obtained from cattle and buffalo (p ≥ 0.05). This high genetic diversity is reflected by the weak phylogenetic clustering of M. bovis from the Lower Amazon River region based on geographic proximity and in the detection of only two putative transmission clusters in the region. One of these clusters is the first description of inter-species transmission between cattle and buffalo in the Amazon, bringing implications to the bTB control program. Surprisingly, two M. bovis lineages were detected in our dataset, namely Lb1 and Lb3, constituting the first description of Lb1 in South America. Most of the strains of this study (13/22) and all 15 strains of the Marajó Island carried no clonal complex marker, suggesting that the recent lineage classification better describe the diversity of M. bovis in the Amazon.